Salvatore Sciarrino: from Sei capricci per violino (1975/6) - Vaes, Luk (2023)
Recording of Eliott Bougant's performance of Sciarrino's Sei Capricci.
FRIS
Editorial review
Keywords: HIPEX: Historical Performance Practices of Experimental Music